2021
DOI: 10.3390/molecules26216449
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Analytical and Statistical Methods in Order to Optimize Antibacterial Activity of Clary Sage Supercritical Fluid Extracts

Abstract: The extraction of clary sage (Salvia sclarea L.) using supercritical carbon dioxide (SC-CO2) was systematically studied by using thin layer chromatography-direct bioautography (TLC-DB) and response surface methodology (RSM). The three parameters temperature, pressure, and cosolvent ratio were optimized for the maximum antibacterial activity of clary sage extracts against Pseudomonas aeruginosa (P. aeruginosa) and methicillin-resistant Staphylococcus aureus (MRSA). The highest inhibition zone was 7.51 mm for P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Supercritical carbon dioxide was used for the extraction of terpenes from powdered ginger rhizomes (Zingiber officinale) at 40 • C and 115 bar pressure [20] and carotenoids from annatto and fennel seeds (semipreparative scale) [50]. Solvent-assisted SFE was used to isolate the polar aromatic flavor compounds from cinnamon (details in Table 1) [35] and essential oil from clary sage (Salvia sclarea L.) with carbon dioxide containing 2% (v/v) ethanol at 40 • C and 186 bar pressure [51], and aloin and aloe-emodin from Aloe and Aloe-containing products [52]. Aloe-emodin (a trihydroxyanthracenedione) and aloin (a C-glycosylated derivative of aloe-emodin) are polar compounds only poorly extracted by supercritical fluid carbon dioxide.…”
Section: Paniculatementioning
confidence: 99%
See 1 more Smart Citation
“…Supercritical carbon dioxide was used for the extraction of terpenes from powdered ginger rhizomes (Zingiber officinale) at 40 • C and 115 bar pressure [20] and carotenoids from annatto and fennel seeds (semipreparative scale) [50]. Solvent-assisted SFE was used to isolate the polar aromatic flavor compounds from cinnamon (details in Table 1) [35] and essential oil from clary sage (Salvia sclarea L.) with carbon dioxide containing 2% (v/v) ethanol at 40 • C and 186 bar pressure [51], and aloin and aloe-emodin from Aloe and Aloe-containing products [52]. Aloe-emodin (a trihydroxyanthracenedione) and aloin (a C-glycosylated derivative of aloe-emodin) are polar compounds only poorly extracted by supercritical fluid carbon dioxide.…”
Section: Paniculatementioning
confidence: 99%
“…It contained visibly less colored material, and no further clean‐up was required prior to HPTLC analysis. It should be noted that several of the above studies demonstrated the preservation of biological activity of the extracts by HPTLC‐bioautography [20, 47, 48, 51]…”
Section: Solvent Extraction (Solids)mentioning
confidence: 99%